Strategic planning and factors affecting the Selection of Manpower strategy Study on Production, Industrial and Service Institutions - Nawar, Ammar Hadi; slim, Chokri (Journal of Ecohumanism, 2024)
This study examines the relationship between strategic planning and the selection of labor in industrial, manufacturing, and service organizations. Surveys were employed in the cross-sectional research for the study. The results of this study add to the body of knowledge about strategic planning and its effects on institution efficiency with regard to production and services, both directly and indirectly. The preparation of strategies and personnel selection have a major impact on production and service quality, as shown by an analysis of the replies from 500 participants.